Unintended but Consequential? The NoG20 Protests in Hamburg and the Introduction of a Police Identification Statute - Fischer, Dorte (PARTECIPAZIONE E CONFLITTO, 2021)
Scholars examining the effects of collective action on public policy have predominantly analyzed policy outcomes with respect to the stated goals of collective actors. This approach to the political influence of collective action not only limits our analytical scope, but also makes the field vulnerable to the criticism that outcome research may be overly deterministic in attributing observed changes to collective action, especially if it utilizes an atemporal logic. This article offers an alternative approach by analyzing a change in legislation that can be considered an unintended consequence of collective action. It examines the decision to introduce a police identification statute after the violent NoG20 protests in Hamburg in 2017 and asks how the protests were consequential for a policy that collective actors had neither initially addressed, nor intended to change. Policy making is conceptualized as a contingent, non-linear process that is best understood from a "processual" perspective. Based on parliamentary documents and semi-structured interviews, the article temporally reconstructs a policy process that had its beginning well before the NoG20 protests. The long-term analysis shows that instead of initiating policy change, the protests created a "window of opportunity" for the members of parliament to push for a proposal they had previously introduced. Police identification was raised after multiple, contingent processes converged after the protests that enabled the members of parliament to point to a factual necessity for policy change. Activists only had a passive role in this change as they had lost credibility during the violent protests. This study emphasizes the centrality of temporality for understanding policy effects of collective action and argues that a processual perspective allows for contextualizing the influence of collective actors both in time and in concert with other actors.